Determination of Caffeine and Taurine Contents in Energy Drinks by HPLC-UV - Rai, Krishna Prasad; Rai, Hasta Bahadur; Dahal, Santosh; Chaudhary, Saroj; Shrestha, Suraj (Journal of Food Science and Technology Nepal, 2016)
Energy drinks are non-alcoholic beverage intended to enhance the psycho-physiological responses in human, which is especially popular among young generation in Nepal. It is normally high caffeinated drink added with other ingredients such as carbohydrates, amino acids, B-group of vitamins etc. In this study, 10 brands of energy drink available in Nepalese markets were taken then analyzed for quantitative determination of Caffeine and Taurine by HPLC-UV method. From the result obtained, pH and TSS values of energy drinks were found in the range of 2.96-3.81 and 6.64-18.21 respectively. Likewise, the Caffeine and Taurine content in same samples were found in the range of not detected (ND) to 35.78 mg/100 ml and ND to 387.5 mg/100 ml respectively. Only the 6 samples out of 10 were confi rmed caffeine content as per claimed in label, while only 3 samples were confi rmed for Taurine content as per label claimed. Based on this pilot study, the majority of samples did not meet the label claims in term of Caffeine and Taurine, which apparently indicated the misbranding of such drinks. Since, there is no any regulation for such energy drinks in Nepal, it seems to be a great challenge for regulation of their safety and misbranding.